If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x+4=-(-2x+6)
We move all terms to the left:
2x+4-(-(-2x+6))=0
We calculate terms in parentheses: -(-(-2x+6)), so:We get rid of parentheses
-(-2x+6)
We get rid of parentheses
2x-6
Back to the equation:
-(2x-6)
2x-2x+6+4=0
We add all the numbers together, and all the variables
10!=0
There is no solution for this equation
| 3x×3=71 | | 10d-34=3d+29 | | 41-4y=5 | | 3(2-x)=2x-9 | | |5x+3|=7 | | x²-13=29 | | 6m=64 | | 2x-3+4(3x-12)-2(4x-9)=x+4 | | -24=12(-x-8) | | (15x+4)/4=11 | | x÷2=5/6 | | 3(2x–4)=2(x+14) | | 8(2d-3)=3(4d-3) | | 2(5x+2)=4(2x+2) | | 2r-5/3=r+1/2 | | 4y-21=24 | | 3j/4+2=8 | | 8k-14=3k+16 | | 5y-8=3y-3 | | 4(x+3)=7x+3-3x | | -9+10(j+11)=-7 | | -3x+6=8x-3x | | 4(x+3)=7x+3-3x= | | 4(2p+1)=34-2p | | -5w+9w=16-48 | | 1-x/6+2x/3-1-7x/4=13/6 | | X=15-n/2 | | -15x+21=-19-5x | | 2(c+14)=8 | | 2w–13=–9 | | 8x/3=5x/2 | | –2(y–10)=–12 |